2023
DOI: 10.1002/bse.3528
|View full text |Cite
|
Sign up to set email alerts
|

The reputational costs of corporate environmental underperformance: evidence from China

Md Mosharraf Hossain,
Lafang Wang,
Jing Yu

Abstract: This study evaluates the relative importance of regulative and reputational pressures on corporate environmental performance by exploiting a novel research setting in China, where the financial penalties for corporate environmental wrongdoing are small. Despite the small monetary penalties, we still document a surprisingly strong negative stock price reaction to the news of corporate environmental violations. Additionally, we show that the negative stock market reaction weakens in firms with strong voluntary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Current event studies have confirmed the negative impact of governmental penalties for corporate environmental irresponsibility on the firm market value (Bouzzine, 2021;Hossain et al, 2023). Governmental penalties have been argued to undermine firm legitimacy (Shevchenko, 2021).…”
Section: Operational Disruption and Non-disruption Penalties And Legi...mentioning
confidence: 91%
“…Current event studies have confirmed the negative impact of governmental penalties for corporate environmental irresponsibility on the firm market value (Bouzzine, 2021;Hossain et al, 2023). Governmental penalties have been argued to undermine firm legitimacy (Shevchenko, 2021).…”
Section: Operational Disruption and Non-disruption Penalties And Legi...mentioning
confidence: 91%
“…Given the availability of data and following Christensen et al (2022) and Serafeim and Yoon (2023), we measure ESG rating divergence based on three prominent rating agencies including Hexun, RKS, and Bloomberg. These datasets have been widely used in top journals addressing Chinese sustainability (see e.g., Chen & Xie, 2022; He et al, 2022; Hossain et al, 2023; Li W. et al, 2023; Wang, Chen, et al, 2023). Consistent with the findings of Berg et al (2022), these ratings differ significantly in terms of indicator scope, weight allocation, and measurement method, which may lead to different rating outcomes for the same company.…”
Section: Methodsmentioning
confidence: 99%
“…This frame of reference is evidenced in examples such as the search for a circular supply chain (Härri et al, 2023), innovation towards a sustainable industry (Narkhede et al, 2023), the application of this modality in companies with different size (small, medium and large) (Madrid-Guijarro & Duréndez, 2023), and the reformulation of types of company according to their integration to these objectives (Riso et al, 2023). Said transversality is also evidenced in CSR actions, which are visible in the regulation of environmental impact (Panda & Kanti, 2023;Wulansari & Adhariani, 2023), the attention in favor of the surrounding community (Patil & Vhavale, 2022), the influence of companies in the economic development of their regions (Zhakupov et al, 2022), and the participation of the government itself to promote better practices (Hossain et al, 2023). All these proposals arise in a global scenario in which companies with profit-oriented purposes are questioned, and others are raised in which participation oriented towards society and the environment is promoted.…”
Section: The Importance and Challenges Of Sdgs And Csrmentioning
confidence: 99%